2022
DOI: 10.1186/s12887-022-03225-1
|View full text |Cite
|
Sign up to set email alerts
|

Mortality reduction in pediatric patients with severe fatal human adenoviral pneumonia treated with high titer neutralizing antibodies (NAbs) plasma: a retrospective cohort study

Abstract: Background Severe fatal human adenoviral (HAdV) pneumonia is associated with significant mortality and no effective drug is available for clinical therapy. We evaluated the association and safety of high titer neutralizing antibodies (NAbs) plasma in pediatric patients with severe fatal HAdV pneumonia. Methods A retrospective cohort study was performed between January 2016 to June 2021 in pediatric intensive care unit. Pediatric patients with sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Meanwhile, plasma therapy has a repair and colloidal support effect on endothelial cells, which is impaired in critically ill patients ( 134 ). A retrospective cohort study conducted by Hongyan Peng et al demonstrated that the administration of high-titer neutralizing antibodies caused faster recovery of body temperature and reduced mortality ( 135 ). High-titer neutralizing antibody therapy has shown efficacy in pediatric adenovirus pneumonia, but its source, optimal dose, and most effective application timing have not been further investigated ( 136 , 137 ).…”
Section: Therapymentioning
confidence: 99%
“…Meanwhile, plasma therapy has a repair and colloidal support effect on endothelial cells, which is impaired in critically ill patients ( 134 ). A retrospective cohort study conducted by Hongyan Peng et al demonstrated that the administration of high-titer neutralizing antibodies caused faster recovery of body temperature and reduced mortality ( 135 ). High-titer neutralizing antibody therapy has shown efficacy in pediatric adenovirus pneumonia, but its source, optimal dose, and most effective application timing have not been further investigated ( 136 , 137 ).…”
Section: Therapymentioning
confidence: 99%